Tengsl offitu við árangur kransæðahjáveituaðgerða - Sæmundur J. Oddsson; Hannes Sigurjónsson; Sólveig Helgadóttir; Martin I. Sigurðsson; Sindri Aron Viktorsson; Þórarinn Arnórsson; Tómas Guðbjartsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2011)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) Introduction: Obesity has been related to increased postoperative morbidity and mortality following open-heart surgery. However, recent studies have shown no association or even a more favourable outcome in obese patients. This relationship was investigated in a well-defined cohort of patients that underwent myocardial revascularisation in Iceland. Material and methods: A retrospective study including all patients that underwent isolated myocardial revascularisation in Iceland from 2002 to 2006. Alltogether 720 patients were divided into two groups, an obese group, with BMI >30 kg/m2 (n=207, 29%), and a non-obese group with BMI ≤30 kg/m2 (n=513, 71%). Patient demographics, complications, operative mortality and long term survival of both groups were compared. Results: Demographics were comparable between the groups. Obese patients were 2.4 years younger, more likely to use statins (83,3% vs. 71,2%, had a significantly lower EuroSCORE (4.3 vs. 5.0) but a slightly longer operation time. Pleural fluid was less often drained in obese patients (8.2 vs. 15.0%) but rates for other complications were similar in both groups, as was operative mortality ≤30 days (2.0% vs. 3.7%), 1 and 5 year survival. In a multivariate analysis obesity was not an independent risk factor for minor or major complications, operative mortality or long term survival. Conclusion: The rate of complications and operative mortality after myocardial revascularisation is not significantly higher in obese patients and the same applies to long term survival. This is true even after correcting for confounding factors in a multivariate analysis. Tilgangur: Offita hefur almennt verið talin auka tíðni fylgikvilla eftir skurðaðgerðir. Niðurstöður rannsókna á tengslum offitu við opnar hjartaaðgerðir eru þó misvísandi og til eru rannsóknir sem sýna sambærilega og jafnvel lægri tíðni fylgikvilla. Tilgangur þessarar rannsóknar var að kanna tengsl ...